THE DIETARY ANIMAL-TO-PLANT SPECTRUM AND CARDIOVASCULAR HEALTH: A NARRATIVE REVIEW - Lamparski, Łukasz; Modrzejewska, Wiktoria; Szmit, Grzegorz; Wcisło, Zofia; Basak, Weronika; Chmielewska, Maria; Piekarska, Patrycja; Purwin, Adrianna; Siwiec, Katarzyna; Lach, Karolina; Kułach, Anna; Krok, Gabriela (International Journal of Innovative Technologies in Social Science, 2026)
Cardiovascular diseases (CVD) remain the leading cause of morbidity and mortality worldwide. Although dietary patterns play a significant role in cardiovascular health, the consumption of meat - particularly red and processed varieties - has increased substantially in recent decades, raising concerns about potential long-term health implications. Large-scale epidemiological studies and meta-analyses consistently link high consumption of red and processed meats to increased risks of cardiovascular disease, stroke, type 2 diabetes, and all-cause mortality. In contrast, dietary patterns rich in plant-based foods, including the Mediterranean diet and other plant-based regimens, are consistently associated with protective effects against cardiovascular diseases. These benefits are likely attributable to their high content of fiber, antioxidants, polyphenols, and omega-3 fatty acids, although findings from observational studies may be influenced by residual confounding. This narrative review aims to integrate findings from epidemiological studies, biomarker research, clinical trials and mechanistic investigations to critically evaluate the cardiovascular health impacts of meat-based diets in comparison to other dietary patterns.